Psychological and physiological state of bioenergetics of hockey players at the beginning of a hockey match that affects the result of playing activity - Sivakov, V. I.; Tumaseva, Z. I.; Belousova, N. A.; Fomina, L. B.; Pyastolova, N. B. (International Journal of Applied Exercise Physiology, 2020)
The purpose of the study: rationale primigravida energy state of the players on the outcome of the hockey match of the continental hockey League. Material and methods: analysis of scientific-methodical literature, concerning the experiment, analysis and synthesis of information, method of mathematical statistics. The study applied the methods of quantum evaluation of energy and functional status of hockey teams Avangard and Traktor. Quantum method is a contact measurement bioenergiesysteme hockey teams Avangard and Traktor, used for diagnosis, evaluation of recovery of functional status during and after the game the training and the competitive activities. Have hockey teams Avangard and Traktor was determined by performance in competitive activity: functional status, recovery process, color, energy level in competitive activity. Results: Identify the color of the energystate hockey teams is the basis for prediction of successful competitive activity. Consider the energy condition and results of operations dependent on the color grid, the functional status of hockey teams, hockey match Avangard -Traktor. The energy system of the hockey teams of the Vanguard and Tractor before the start of the match was different in color energy state and, accordingly, the functional preparedness of the game activity, the game result of the hockey match was different.In conclusion, we note that effective hockey teams in game matches will have a bright red, red energy potential in the form of a circle, rather than a horizontal square with green, yellow, blue, brown color of energy, indicating vague fuzzy outlines of energy, which confirms fatigue, overwork, overstrain, leading to the loss of the hockey team.